PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ULANG KEBAYA PADA RUMAH KEBAYA BALI MOLEK - Tanzil, Felycia Errina; Kusuma, A. A. G. Agung Artha (E-Jurnal Manajemen, 2015)
In Indonesia, the development of fashion very quickly and very large especially in kebaya fashion. Business attire is very much favored by Indonesian woman who is predicted to have a very profitable market opportunities. There are many businesses in the kebaya fashion Denpasar Bali in particular, one of which is the House of Bali Kebaya Molek. Repurchasing the purchasing process whereby consumers are satisfied with the products they consume. My  studyies it’s conducteded until determineded the effect of the marketing mix to re-purchase decision in the House of Bali Kebaya Molek. My ressearch it’s conducteded at Denpasar, the samples taken were 112 redpondencaes used the purposive sampling method. The date it’s collected througgh questionnaires used the linear regression analysis. Based on the results showed that each variable product, price, promotion, and place a significant effect on the purchase decision again.
Keywords: Product, Price, Promotion, Place, and Repeat Purchase